2014
DOI: 10.1055/s-0034-1378189
|View full text |Cite
|
Sign up to set email alerts
|

Outcome after Preoperative or Intraoperative Use of Intra-arterial Urokinase Thrombolysis for Acute Popliteal Artery Thrombosis and Leg Ischemia

Abstract: Our results suggest that the immediate surgery with intraoperative thrombolysis improved the outcome of patients with acute leg ischemia due to PAA thrombosis in terms of limb salvage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…28 Concerning acute popliteal artery aneurysm thrombosis and leg ischemia, a study analyzed the outcomes of preoperative and intraoperative use of intra-arterial thrombolysis reporting 30-day amputation rates of 18% and 29%, respectively. 7 Leak et al reported on 186 popliteal aneurysms (110 OR, 76 ER). OR was performed in more patients with thrombosis (41.8% vs 5.3%; p < .001), acute ischemia (24.5% vs 9.2%; p < .010), and ischemic rest pain (34.5% vs 6.6%; p < .001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Concerning acute popliteal artery aneurysm thrombosis and leg ischemia, a study analyzed the outcomes of preoperative and intraoperative use of intra-arterial thrombolysis reporting 30-day amputation rates of 18% and 29%, respectively. 7 Leak et al reported on 186 popliteal aneurysms (110 OR, 76 ER). OR was performed in more patients with thrombosis (41.8% vs 5.3%; p < .001), acute ischemia (24.5% vs 9.2%; p < .010), and ischemic rest pain (34.5% vs 6.6%; p < .001).…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Moreover, studies reporting on the use of fibrinolysis in the acute treatment of PAA have been published. 7 Recent guidelines from the Society of Vascular Surgery recommend a stratification of thrombotic or embolic complications of PAA depending on the severity of ischemia at presentation to decide if a thrombolysis or pharmacomechanical intervention should be performed. 8 Only one randomized controlled trial exists comparing OR with ER for elective asymptomatic PAA.…”
mentioning
confidence: 99%
“…There are 3 generations of thrombolytic agents: the first (streptokinase, urokinase), the second (alteplase and pro-urokinase), and the third (reteplase, tenecteplase, and staphylokinase). Even though streptokinase, urokinase, and alteplase are frequently used inperipheral arterial diseases, recent guidelines recommend the last 2 thrombolytics [9] , [10] - 11] !. The treatment dose of alteplase is a bolus of 1-2 mg followed by infusion of 0.05 mg/kg/h and 10,000 UI of intravenous heparin per 24 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Common thrombolytic agents include first generation agents, such as streptokinase and urokinase, second generation agents, such as tissue plasminogen activator (tPA) and pro urokinase, and third generation agents, including reteplase, tenecteplase and Staphylokinase. Thrombolytic agents utilized in the treatment of peripheral arteries disease include streptokinase and urokinase as well as, currently, alteplase (15) .…”
Section: Thrombolytic Agent Practical Definitionmentioning
confidence: 99%